Traumatic uterine rupture following instrumental delivery - Patil, Sanika; Mittal, Stuti; Sharma, Sunil; Gabhane, Sameeksha (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2024)
Uterine rupture is a very rare but critical obstetric complication that requires prompt diagnosis and treatment. An instrumental vaginal delivery refers to an obstetrical procedure in which active measures are taken to accomplish a normal delivery by applying traction on the foetal head by using forceps or vacuum. If all the prior pre requisitions required for an instrumental delivery are not met, it can lead to disastrous complications like a uterine rupture. Here’s presenting a case of a 32-year-old female, para 2 living 2 with uterine rupture following instrumental vaginal delivery. This led to traumatic postpartum haemorrhage that required further surgical evaluation and management. There are potential risks associated with instrumental deliveries and there is a need for vigilance in managing and monitoring potential complications. If all the prior requisites are not met it can lead to uterine rupture which can be avoided. In this case the combined efforts of intensivists, obstetric and cardiovascular surgeons ensured the preservation of the uterus, which is notable given the extent of injury. The preservation of the uterus is noteworthy, as uterine rupture often necessitates hysterectomy to manage uncontrolled haemorrhage or severe damage. It also contributes to the medical literature by detailing an exceptional instance of uterine rupture due to vacuum assisted delivery, providing valuable insights for future clinical practice.